2020
DOI: 10.1177/2150135120947687
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Printing of Fetal Heart With d-Transposition of the Great Arteries From Ultrasound Imaging Data

Abstract: We reconstructed and printed a 3D model of the fetal heart affected by d-transposition of the great arteries from prenatal ultrasound images. Our 3D model revealed to be very helpful in showing the basic anatomical features of fetal complex Congenital Heart Disease (CHD) and represents an interesting additional diagnostic tool to the current standard imaging armamentarium, improving the quality of prenatal parental counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The 3D physical models of the fetal heart can reproduce the anatomic structures and spatial relationship of the fetal heart in a real and clear manner; the abnormal parts can be visually displayed and diagnosed clearly 1 . The 3D model represents an interesting additional diagnostic tool to the current standard imaging armamentarium, improving the quality of prenatal parental counseling mainly in complex CHD such as Ebstein's anomaly and tricuspid dysplasia or Taussig‐Bing and transposition of the great arteries with ventricular septal defect, which also differ in their postnatal outcome and management 2 . 3D physical and virtual models of the fetal heart can also be a useful tool for teaching cardiovascular anatomy, including the development of 3D ultrasound applications and software development 3,4 …”
Section: Figurementioning
confidence: 99%
“…The 3D physical models of the fetal heart can reproduce the anatomic structures and spatial relationship of the fetal heart in a real and clear manner; the abnormal parts can be visually displayed and diagnosed clearly 1 . The 3D model represents an interesting additional diagnostic tool to the current standard imaging armamentarium, improving the quality of prenatal parental counseling mainly in complex CHD such as Ebstein's anomaly and tricuspid dysplasia or Taussig‐Bing and transposition of the great arteries with ventricular septal defect, which also differ in their postnatal outcome and management 2 . 3D physical and virtual models of the fetal heart can also be a useful tool for teaching cardiovascular anatomy, including the development of 3D ultrasound applications and software development 3,4 …”
Section: Figurementioning
confidence: 99%
“…Another interesting recent application is the use of this technology for preoperative counseling [8,9]. This has proved particularly useful in the pediatric world to explain and raise awareness among parents about the diseases affecting their children.…”
Section: The Use Of 3d Printing and Virtual Realitymentioning
confidence: 99%
“…With advances in STIC, the derived data can be used for 3D printing of the fetal heart, which is a fast-moving structure [ 60 ]. In a recent case report, the authors found that the 3D model was useful in showing the complex anatomy of fetal transposition of great arteries and in providing prenatal parental counseling [ 61 ].…”
Section: 3d/4d Ultrasoundmentioning
confidence: 99%